Party Finance Regulation: Causes, Instruments and Impact - Zdravko PETAK (Acta Universitatis Danubius: Juridica, 2015)
Money has a symbolic and practical value in political competition and just because the money is important in politics, it can threaten democracy if its role is not adequately regulated. The basic features of party finance regulation will be shown in this paper: causes, instruments and impact. The regulation of party finances began in 1960s and the causes of the party finance regulation were different: in addition to the prevention of corruption scandals related to political parties and party finance, regulation of party finance has also been introduced to strengthen fair political competition, empower voters and strengthen political parties as effective democratic actors. To achieve this whole range of policy instruments was developed, whose scope extends from ways of regulating the possibility of buying votes, to limit election campaigns expenditure costs. However, impact of party finance regulation is not unambiguous since, due to the regulatory traditions and cultural attitudes, similar instruments of party finance regulation produce different results in different political systems.